Molecular and isotopic partitioning of low-molecular-weight hydrocarbons during migration and gas hydrate precipitation in deposits of a high-flux seepage site. - Pape, Thomas; Bahr, André; Rethemeyer, Janet; Kessler, John D; Sahling, Heiko; Hinrichs, Kai-Uwe; Klapp, Stephan A; Reeburgh, William S; Bohrmann, Gerhard (PANGAEA, 2010)
Detailed knowledge of the extent of post-genetic modifications affecting shallow submarine hydrocarbons fueled from the deep subsurface is fundamental for evaluating source and reservoir properties. We investigated gases from a submarine high-flux seepage site in the anoxic Eastern Black Sea in order to elucidate molecular and isotopic alterations of low-molecular-weight hydrocarbons (LMWHC) associated with upward migration through the sediment and precipitation of shallow gas hydrates. For this, near-surface sediment pressure cores and free gas venting from the seafloor were collected using autoclave technology at the Batumi seep area at 845 m water depth within the gas hydrate stability zone. Vent gas, gas from pressure core degassing, and from hydrate dissociation were strongly dominated by methane (>99.85 mol.% of Sum[C1-C4, CO2]). Molecular ratios of LMWHC (C1/[C2 + C3] > 1000) and stable isotopic compositions of methane (d13C = -53.5 per mill V-PDB; D/H around -175 per mill SMOW) indicated predominant microbial methane formation. C1/C2+ ratios and stable isotopic compositions of LMWHC distinguished three gas types prevailing in the seepage area. Vent gas discharged into bottom waters was depleted in methane by >0.03 mol.% (Sum[C1-C4, CO2]) relative to the other gas types and the virtual lack of 14C-CH4 indicated a negligible input of methane from degradation of fresh organic matter. Of all gas types analyzed, vent gas was least affected by molecular fractionation, thus, its origin from the deep subsurface rather than from decomposing hydrates in near-surface sediments is likely. As a result of the anaerobic oxidation of methane, LMWHC in pressure cores in top sediments included smaller methane fractions [0.03 mol.% Sum(C1-C4, CO2)] than gas released from pressure cores of more deeply buried sediments, where the fraction of methane was maximal due to its preferential incorporation in hydrate lattices. No indications for stable carbon isotopic fractionations of methane during hydrate crystallization from vent gas were found. Enrichments of 14C-CH4 (1.4 pMC) in short cores relative to lower abundances (max. 0.6 pMC) in gas from long cores and gas hydrates substantiates recent methanogenesis utilizing modern organic matter deposited in top sediments of this high-flux hydrocarbon seep area.
Gas analysis of sediment cores from the Batumi seep area
Keywords: Batumi Seep; Center for Marine Environmental Sciences; DAPC; DAPC-1; DAPC-12; DAPC-14; DAPC-15; DAPC-16; DAPC-2; DAPC-3; DAPC-8; DAPC-9; Dynamic autoclave piston corer; Gas bubble sampler; GBS; GBS-3; GBS-4; GBS-5; GBS-8; GC; GC-13; GC-14; GC-18; GC-23; GC-4; GC-6; GC-8; GeoB11901; GeoB11903; GeoB11904-16; GeoB11906; GeoB11907-2; GeoB11907-5; GeoB11918; GeoB11919; GeoB11920; GeoB11921-1; GeoB11925; GeoB11927; GeoB11936; GeoB11937; GeoB11946; GeoB11949; GeoB11951; GeoB11956; GeoB11958; GeoB11963; GeoB11975; Gravity corer; M72/3a; M72/3b; MARUM; Meteor (1986); Remote operated vehicle; ROV; ROV-8